2017
DOI: 10.1016/j.jcp.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Galerkin v. least-squares Petrov–Galerkin projection in nonlinear model reduction

Abstract: Least-squares Petrov-Galerkin (LSPG) model-reduction techniques such as the Gauss-Newton with Approximated Tensors (GNAT) method have shown promise, as they have generated stable, accurate solutions for large-scale turbulent, compressible flow problems where standard Galerkin techniques have failed. However, there has been limited comparative analysis of the two approaches. This is due in part to difficulties arising from the fact that Galerkin techniques perform optimal projection associated with residual min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
257
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(266 citation statements)
references
References 56 publications
(91 reference statements)
6
257
0
Order By: Relevance
“…The SINDy framework has been recently generalized by Loiseau and Brunton [39] to incorporate known physical constraints and symmetries in the equations by implementing a constrained sequentially thresholded leastsquares optimization. Such constraints are known to promote stability [46][47][48]. Loiseau et al [49] also demonstrated the ability of SINDy to identify dynamical systems models of high-dimensional systems, such as fluid flows, from a few physical sensor measurements.…”
Section: Sindy: Sparse Identification Of Nonlinear Dynamicsmentioning
confidence: 99%
“…The SINDy framework has been recently generalized by Loiseau and Brunton [39] to incorporate known physical constraints and symmetries in the equations by implementing a constrained sequentially thresholded leastsquares optimization. Such constraints are known to promote stability [46][47][48]. Loiseau et al [49] also demonstrated the ability of SINDy to identify dynamical systems models of high-dimensional systems, such as fluid flows, from a few physical sensor measurements.…”
Section: Sindy: Sparse Identification Of Nonlinear Dynamicsmentioning
confidence: 99%
“…A similar technique utilizing approximation instead of interpolation is the gappy POD . Other hyperreduction techniques are the energy conserving sampling and weighting (ECSW) and the Gauss‐Newton with approximated tensors (GNAT) …”
Section: Projection‐based Model Order Reductionmentioning
confidence: 99%
“…[1], [4]) of the first-order system (4) by setting u ≈ V u z u , v ≈ V v z v and w ≈ V w z w , i.e. by separately projecting the position, velocity and pressure DOFs.…”
Section: Reduced Modelmentioning
confidence: 99%
“…The equations describing the muscle deformation over time are the balance of linear momentum subject to the incompressibility constraint ρ 0 (X ) ∂V ∂t (X , t) = ∇ · P(X , t) + B(X , t) , s.t. J(X , t) = 1 , ∀ X ∈ Ω 0 , (1) and a nonlinear constitutive equation of the form P(X , t) = P iso (X , t) + P aniso (X , t) + P act (X , t) + P visc (X , t)…”
mentioning
confidence: 99%
See 1 more Smart Citation